Cretaceous ammonite distributions and the opening of the South Atlantic - Kennedy, W; Cooper, M (1975)
Analysis of distribution patterns of middle to late Cretaceous ammonites along the line of the opening S. Atlantic suggest that open marine connections, if not actual rifting developed during early upper Albian times and extended continuously to the close of the Cenomanian. Evidence of early Turonian distributions is equivocal (due largely to an absence of early Turonian marine deposits in Southern Africa), but such evidence as is available also suggests continued connection. Palaeobiogeographic evidence is thus corndevelop patible with sea floor spreading and palaeo magnetic data, rather than in conflict, as previously suggested.